Methods and Applications in Respiratory Physiology: Respiratory Mechanics, Drive and Muscle Function in Neuromuscular and Chest Wall Disorders - Patel, Nina; Chong, Kelvin; Baydur, Ahmet (Frontiers in Physiology, 2022)
Individuals with neuromuscular and chest wall disorders experience respiratory muscle weakness, reduced lung volume and increases in respiratory elastance and resistance which lead to increase in work of breathing, impaired gas exchange and respiratory pump failure. Recently developed methods to assess respiratory muscle weakness, mechanics and movement supplement traditionally employed spirometry and methods to evaluate gas exchange. These include recording postural change in vital capacity, respiratory pressures (mouth and sniff), electromyography and ultrasound evaluation of diaphragmatic thickness and excursions. In this review, we highlight key aspects of the pathophysiology of these conditions as they impact the patient and describe measures to evaluate respiratory dysfunction. We discuss potential areas of physiologic investigation in the evaluation of respiratory aspects of these disorders.